Alternate expression of CONSTANS-LIKE 4 in short days and CONSTANS in long days facilitates day-neutral response in Rosa chinensis - Lu, Jun (J Exp Bot, 2020)
Photoperiodic flowering responses are classified into three major types: long day (LD), short day (SD), and day neutral (DN). The inverse responses to daylength of LD and SD plants have been partly characterized in Arabidopsis and rice; however, the molecular mechanism underlying the DN response is largely unknown. Modern roses are economically important ornamental plants with continuous flowering (CF) features, and are generally regarded as DN plants. Here, RcCO and RcCOL4 were identified as floral activators up-regulated under LD and SD conditions, respectively, in the CF cultivar Rosa chinensis ‘Old-Blush’. Diminishing the expression of RcCO or/and RcCOL4 by virus-induced gene silencing (VIGS) delayed flowering time under both SDs and LDs. Interestingly, in contrast to RcCO-silenced plants, the flowering time of RcCOL4-silenced plants was more delayed under SD than under LD conditions, indicating perturbed plant responses to day neutrality. Further analyses revealed that physical interaction between RcCOL4 and RcCO facilitated binding of RcCO to the CORE motif in the promoter of RcFT and induction of RcFT. Taken together, the complementary expression of RcCO in LDs and of RcCOL4 in SDs guaranteed flowering under favorable growth conditions regardless of the photoperiod. This finding established the molecular foundation of CF in roses and further shed light on the underlying mechanisms of DN responses.